Pengaruh Pengeluaran Zakat Perbankan, Ukuran Perusahaan dan Islamic Social Responsibility (ISR)Terhadap Profitabilitas Pada Bank Umum Syariah di Indonesia Periode 2017-2022 - Agustin, Shinta Dwi; Rosyidah, Norma (Jurnal EMT KITA, 2024)
This research aims to investigate the impact of zakat expenditure by banks, company size, and Islamic social responsibility on profits. This research data was obtained from the annual financial report (Annual Report) of sharia commercial banks for the 2017-2022 period. The research method used is quantitative with data analysis using a multiple linear regression model. Hypothesis testing is carried out through partial tests (T test) and simultaneous tests (F test) with a significance level of 5%. Simultaneous test results show that bank zakat expenditure, company size, and ISR together have a positive and significant effect on profits. Partially, the bank zakat expenditure variable shows a positive and significant effect on profits, while company size and ISR do not have a significant effect on profits of sharia commercial banks. Testing each independent variable on the dependent variable shows that the zakat expenditure variable (X1) does not have a positive and significant effect on profit (Y). Company size (X2) has a partial effect on profit (Y) with a significant signature value. On the other hand, the ISR variable (X3) does not have a significant influence on profits (Y) in Islamic commercial banks in Indonesia.